TRENDS AND CHALLENGES IN THE ECONOMIC ENVIRONMENT – FOOD INDUSTRY. WHAT S NEXT? - ALEXANDRA ȚÂRĂU; EMIL MUNTEAN; BEATRICE ELENA GORE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Considering the challenges that Romania is currently facing in the food industry, we can say that it is a topic of interest and topicality to be subjected to a thorough research. The general objective for the present scientific approach is the current trends in the food industry on a regional level. The research questions that come to answer the general research objective are: how the food industry evolved through the challenges of the pandemic and the Ukrainian war ? what is the current situation of the food industry? The food industry is growing, fueled by frequent changes in the behavior of Romanian consumers, so the trade in food and beverages has grown in recent years.